Counter-Extremes Against of Musabaqah Tilawatil Qur’an (MTQ) in Tafsir Al-Iklīl fī ma’āni al-Tanzīl - Ika Hilmiatus Salamah; Yaqin, Ahmad Ainul; Sulaiman; Amin, Nasihun (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This study focuses on the shifting meaning of Musabaqah Tilawatil Qur'an among contemporary mufassirs. This study aims to analyze the verses in Tafsir Al-Iklīl fī Ma'āni al-Tanzīl that talk about Musabaqah Tilawatil Qur'an and some mufassir's views on the phenomenon of Musabaqah Tilawatil Qur'an. The method used is library research with a descriptive-analytical approach and the use of thematic verses. The results of this study show two understandings. First, the view of the rejection of the practice of Musabaqah Tilawatil Qur'an in tafsir Al-Iklīl fī the grounds that these activities can be used as a medium for Islamic propagation and preaching Ma'āni al-Tanzīl by Misbah Musthofa because it is considered to contain elements of riya', materialism and deviation from spiritual values. Second, Buya Hamka's view that supports Musabaqah Tilawatil Qur'an on, as long as it maintains adab and does not ignore the main purpose of reciting the verses of Qur'an.